2017
DOI: 10.1002/2017tc004600
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic formation and stabilization of Archean lithosphere by accretionary orogenesis: Constraints from TTG and potassic granitoids, North China Craton

Abstract: Accretionary orogens are major sites of modern continental growth, yet their role in the development of Archean continental crust remains enigmatic. Diverse granitoid suites from tonalite‐trondhjemite‐granodiorite (TTG) to potassic granitoids appeared during late Archean, representing a period of major continental formation and stabilization. In this study, whole‐rock geochemical and zircon U‐Pb and Lu‐Hf isotopic data are reported for Neoarchean granitoid gneisses from the Northern Liaoning Terrane, northeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Similar subduction-accretion tectonic model have been put forward for other Archean cratons worldwide (e.g. Cawood et al, 2009;Hawkesworth et al, 2016;Wang et al, 2017;Yu et al, 2019), thus suggesting the emergence of plate tectonics and associated accretionary orogens around 3.2-3.0 Ga (e.g. Hawkesworth et al, 2016;Brenner et al, 2020;reference therein).…”
Section: Geotectonic Evolution Of the Ntem Archean Complexsupporting
confidence: 69%
“…Similar subduction-accretion tectonic model have been put forward for other Archean cratons worldwide (e.g. Cawood et al, 2009;Hawkesworth et al, 2016;Wang et al, 2017;Yu et al, 2019), thus suggesting the emergence of plate tectonics and associated accretionary orogens around 3.2-3.0 Ga (e.g. Hawkesworth et al, 2016;Brenner et al, 2020;reference therein).…”
Section: Geotectonic Evolution Of the Ntem Archean Complexsupporting
confidence: 69%
“…During the Late Neoarchean (2.6–2.5 Ga), the seven micro‐blocks within the NCC began to amalgamate through oceanic subduction and continent‐continent collisions (Figure 1b; Tang & Santosh, 2018; Wan et al, 2015; Zhai, Bian, & Zhao, 2000; Zhai et al, 2005; Zhai, 2014). The NCC underwent extensive tectono‐thermal events during the amalgamation process and generated abundant intrusive rocks in the NCC, including tonalite‐trondhjemite‐granodiorite (TTG), associated with minor gabbroic and dioritic rocks (Gong, Zhang, Yu, Li, & Hou, 2012; Wan et al, 2015, 2017; Wang et al, 2017; Zhai, 2014; Zhou, Zhao, Zhai, Gao, & Sun, 2014). Previous studies identified that widespread magmatic rocks of the Late Neoarchean are distributed in the Jining Block, especially the Daqingshan region and adjacent Guyang area.…”
Section: Discussionmentioning
confidence: 99%
“…Later, they revised the model so that both oceans closed at ~1,880 Ma (Trap et al, ; Trap et al, ). Another group of scholars (Deng et al, ; Deng et al, ; Kusky et al, ; Wang et al, , ; Wang, Cawood, et al, ; Wang, Kusky, et al, ; Wang, Kusky, et al, ) suggested that the WZD belongs to the Fuping arc, and the western part of the CZD (or the Guandu Group) was a ~2.5 Ga tectonic mélange belt and suture between the Eastern Block and the Fuping arc, suggesting an arc–continent collision in the late Neoarchaean. Li, Santosh, Teng, and He (, ) and Tang, Santosh, Tsunogae, and Maruoka (, ) proposed a model in which the Eastern Block and the Zanhuang arc collided at ~2.3 Ga, followed by back‐arc extension and rifting.…”
Section: Discussionmentioning
confidence: 99%
“…The NCC also shows such a distinct transition during 3.0–2.5 Ga period. These granitoids have been studied separately by many scholars (e.g., Diwu et al, ; Fu et al, ; Liu et al, ; Wang et al, ; Wang, Cawood, et al, ; Yang, Wu, Wilde, & Zhao, ). However, a comprehensive study of these diverse granitoids has not been carried out in the central NCC.…”
Section: Introductionmentioning
confidence: 99%